1991
DOI: 10.1128/iai.59.12.4540-4546.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma interferon, tumor necrosis factor alpha, and interleukin-2 on infection and proliferation of Theileria parva-infected bovine lymphoblasts and production of interferon by parasitized cells

Abstract: Theileria parva is a protozoan parasite that infects bovine B cells and aol and y8 T cells and transforms them into continually proliferating cells. CD4+ T. parva-antigen-specific immune T cells have been shown to produce cytokines in response to stimulation with parasitized cells, and T. parva-infected Iymphocytes produce and consume T-cell growth factors and interleukin-2 (IL-2). To ascertain the role of T-cell cytokines on T. parva infections, we evaluated recombinant gamma interferon (rIFN-y), rIL-2, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Pre-treatment with IFN-y can increase the hosts susceptibility to endotoxin with increased serum level of TNF-a and IL-6 [3,23]. On the other hand, exogenous recombinant IFN-y contributes to the resistance in the acute infections caused by Toxoplasma gondi, Leishmania, Ehrlichia, Legionella, Salmonella, Listeria, and Klebsiella [7,[19][20][21][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment with IFN-y can increase the hosts susceptibility to endotoxin with increased serum level of TNF-a and IL-6 [3,23]. On the other hand, exogenous recombinant IFN-y contributes to the resistance in the acute infections caused by Toxoplasma gondi, Leishmania, Ehrlichia, Legionella, Salmonella, Listeria, and Klebsiella [7,[19][20][21][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…A striking feature of the lymphoid hyperplasia observed in primary T. parva infection is that 20-30% of cells leaving the lymph node draining the site of inoculation may be lymphoblasts, of which only 1% may be infected (Emery 1981). T. parva-infected cells have been shown to secrete interferon gamma (IFNg) (DeMartini & Baldwin 1991), express low levels of IL2 (Heussler et al 1992), and constitutively express the a chain of the IL2 receptor (Dobbelaere et al 1990). In addition, there is evidence that their growth is enhanced by both IL2 and IFNg (DeMartini & Baldwin 1991).…”
Section: Introductionmentioning
confidence: 99%
“…T. parva-infected cells have been shown to secrete interferon gamma (IFNg) (DeMartini & Baldwin 1991), express low levels of IL2 (Heussler et al 1992), and constitutively express the a chain of the IL2 receptor (Dobbelaere et al 1990). In addition, there is evidence that their growth is enhanced by both IL2 and IFNg (DeMartini & Baldwin 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the addition of IL-2 to T. parvainfected cells has a differential effect on parasite-host cell development depending on the time of application. For example, two recent studies have shown that IL-2 treatment of newly infected lymphocytes either had no effect on the establishment of infected cell cultures (5) or significantly suppressed the transformation and development of parasiteinfected cells (27). However, in both these reports, the addition of IL-2 to established macroschizont-infected cell lines resulted in enhanced proliferation of the cultures.…”
Section: Discussionmentioning
confidence: 99%